2021
DOI: 10.3899/jrheum.201250
|View full text |Cite
|
Sign up to set email alerts
|

Joint Association of Moderate-to-vigorous Intensity Physical Activity and Sedentary Behavior With Incident Functional Limitation: Data From the Osteoarthritis Initiative

Abstract: Objective To examine joint association of moderate-to-vigorous intensity physical activity (MVPA) and sedentary behavior with the risk of developing functional limitation 4 years later in adults with knee OA. Methods Using 48-month (baseline) accelerometry data from Osteoarthritis Initiative, , we classified participants as Active-Low Sedentary (≥1 10-minute bout/week of MVPA, lowest tertile for standardized sedentary time), Active-High Sedentary (≥1 10-minute bout/week of MVPA, top two tertiles for standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
4
10
0
Order By: Relevance
“…In our study, higher physical activity levels predicted good physical functioning, which is in line with an earlier study in which more time spent in habitual light-intensity physical activity was associated with better lower-extremity performance in community-dwelling older adults [27]. In another study, low physical activity was associated with the development of functional limitations in adults with knee OA [28]. Furthermore, Kraus et al found strong evidence that physical activity improved physical function among individual with hip or knee OA relative to less active adults with OA [29].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, higher physical activity levels predicted good physical functioning, which is in line with an earlier study in which more time spent in habitual light-intensity physical activity was associated with better lower-extremity performance in community-dwelling older adults [27]. In another study, low physical activity was associated with the development of functional limitations in adults with knee OA [28]. Furthermore, Kraus et al found strong evidence that physical activity improved physical function among individual with hip or knee OA relative to less active adults with OA [29].…”
Section: Discussionsupporting
confidence: 92%
“…The MVPA status was categorized as ‘active’ or ‘inactive’ based on meeting the weekly threshold 150 min of MVPA [ 24 ]. Then, the categories of SB and MVPA statuses were combined to formulate the following four mutually exclusive behavioral categories: (1) active-low sedentary, (2) active-high sedentary, (3) inactive-low sedentary and (4) inactive-high sedentary [ 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, a small number of studies have utilized mutually exclusive PA categories to understand the combined effects of PA and SB on different health markers [ 20 , 21 , 22 , 23 ]. For instance, in population-based samples from the United States and England, it was observed that physically active adults, regardless of their sedentary status, had better cardiometabolic health profiles in comparison to those not meeting the MVPA guidelines [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations